A comparative study on Common Object Request Broker Architecture (CORBA) and IBM websphere / Latipah Robaniah Jamaludin - Jamaludin, Latipah Robaniah (2005)
The rapid changes in information technology require the organizations and expertise to be alert about the new inventions of tools, software and hardware. Nowadays, within the assist of technologies most of the organizations processes including government and business company are computerized. There are no more geographically problems to integrate, distribute and share information between organizations. The existing middleware support the needs of organization which have to manage many clients' databases and connect it with other branches, faster response for market demands as well as provide widely networks. This study compares and contrasts the strengths and weaknesses of two middleware known as CORBA and IBM Websphere in term of their fiinctions. This study also proposes the several guidelines to be consider in choosing appropriate middleware before implementing it.